Pengaruh Motivasi Terhadap Produktivitas Kerja Karyawan Pada Perum Bulog Makassar - Nurul Astri; Uhud Darmawan Natsir; Romansyah Sahabuddin; Burhanuddin Burhanuddin; Zainal Ruma (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
In this research, it will be known how Perum employees are motivated Bulog Makassar influences their work productivity level. Entire The number of employees of Perum Bulog Makassar who is the population for this research is: 65 people. By using Statistical Product and Service Solution (SPSS), data analysis techniques were carried out. This type of research uses a cross sectional design and approach analytical observations to ascertain the relationship between drivers of work motivation and work productivity. The data collection techniques used in this research were observation, interviews and questionnaires. Based on the research results, a simple linear analysis was obtainedwith a constant value of x8,451, x means that the dependent variable is motivation (X) has a value of 0, so the influence on work productivity (Y) is equal to 8,451. The regression coefficient for the motivation variable is 0.710. This matter shows how big the influence of motivation is on Perum Bulog's efforts Makassar in encouraging worker productivity.